TERAPI EMOTIONAL FREEDOM TECHNIQUE MENURUNKAN NYERI POST SECTIO CAESAREA - Silaban, Jojor (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
ABSTRACT Background. Every surgery will experience pain, ranging from mild pain to very severe pain. 93% of sectio caesarea (SC) patients experience moderate to severe pain using a visual analog scale (VAS). Pain causes disruption to sleep rest, limited to meeting needs such as self-care, baby care and bounding attachments. Pain is minimized by pharmacological and non-pharmacological approaches. One of them is Emotional Freedom Technique (EFT) therapy. Research purposes. Knowing the effect of EFT therapy on pain in post SC mothers in Sidikalang Regional Hospital. Research methods. This study used a quasi-experimental design with a one group pre-post test design approach. Data collection in the Mawar Room of Sidikalang Regional Hospital with a population of 298 people and a sample of 20 people with incidental sampling technique. Data were analyzed by different paired t test. Research result. Shows that the average pre-test pain in post SC mothers is moderate pain (46.45), and the average post-test pain is mild pain (32.45). Different test results paired t test, pre-test and post-test found 11,570> 1,729 (t arithmetic> t table). From the test results it was found that there are significantly different mean before and after EFT therapy. Conclusion. There is an effect of EFT therapy on pain in post SC mothers. Suggestion. So that health workers are willing and able to do EFT therapy to reduce post SC pain. Keywords: Post Sectio Caesarea Pain, EFT Therapy ABSTRAK Setiap pembedahan akan mengalami nyeri, mulai dari nyeri ringan sampai nyeri sangat berat. Terdapat 93% pasien sectio caesarea (SC) mengalami nyeri sedang sampai dengan berat dengan menggunakan skala analog visual (VAS). Nyeri menyebabkan gangguan istirahat tidur, terbatas memenuhi kebutuhan seperti perawatan diri, pengasuhan bayi dan bounding attachment. Nyeri diminimalkan dengan pendekatan farmakologis dan non-farmakologis. Salah satunya adalah terapi Emotional Freedom Technique (EFT). Tujuan penelitian untuk mengetahui pengaruh terapi EFT terhadap nyeri pada ibu post SC di RSUD Sidikalang. Metode penelitian. Penelitian ini menggunakan desain quasi eksperimen dengan pendekatan one group pre-post test design. Pengumpulan data di Ruang Mawar RSUD Sidikalang dengan jumlah populasi 298 orang dan sampel 20 orang dengan teknik insidental sampling. Data dianalisis dengan uji beda Paired t test. Hasil penelitian. Menunjukkan bahwa rata-rata nyeri pre-test pada ibu post SC yaitu nyeri sedang (46.45), dan rata-rata nyeri post test adalah nyeri ringan (32.45). Hasil uji beda paired t test, pre-test dan post-test didapatkan 11.570>1.729 (t hitung>t tabel). Artinya ada beda secara signifikan rerata sebelum dan sesudah diberikan terapi EFT. Kesimpulan. Ada pengaruh terapi EFT terhadap nyeri pada ibu post SC. Saran. Agar petugas kesehatan mau dan mampu melakukan terapi EFT untuk menurunkan nyeri post SC. Kata Kunci : Nyeri post sectio caesarea, terapi EFT